Perjuangan Sulaiman Ar-Rasulli dalam Mempertahankan Kemerdekaan Indonesia 1945-1949 - Hendra Hendra; Syaiful Anw’ar (Lembaga Yasin AlSys, 2026)
Although many studies have examined the role of ulama in Indonesia’s struggle for independence, research that specifically discusses the contribution of Syekh Sulaiman Ar-Rasuli in defending Indonesian independence during the 1945–1949 period remains limited. This study aims to analyze the role and struggle of Syekh Sulaiman Ar-Rasuli in the fields of education, politics, law, and the social mobilization of Muslims during the independence revolution. This study employed a qualitative approach with a historical research method. Data were obtained through literature study, historical documentation, and field study in Candung by utilizing archives, historical photographs, and related literature. Data analysis was conducted through the stages of heuristics, internal and external source criticism, interpretation, and historiography. The results showed that Syekh Sulaiman Ar-Rasuli played an important role in spreading the spirit of jihad fi sabilillah through the educational institution Madrasah Tarbiyah Islamiyah (MTI) Candung, transforming Persatuan Tarbiyah Islamiyah (PERTI) into a political party, and supporting the establishment of Laskar Muslimin and Laskar Muslimat in defending independence. In addition, his leadership as Chairman of the Mahkamah Syar’iyah of Central Sumatra also played a role in maintaining social stability and the implementation of Islamic law during the transition to independence. These findings enrich historiographical studies on the role of ulama in the national struggle and demonstrate the strategic contribution of ulama to the formation of the socio-political structure of society in the early period of Indonesian independence.